Enhancing radiation protection at Sirius: methodology and results of beamline training - Ana Luísa da Costa Vieira; Fernanda do Nacimento Moura (Brazilian Journal of Radiation Sciences)
This work is about radiation protection training at Sirius, a unique radiation facility in Brazil for being a synchrotron-type particle accelerator. Research in several areas takes place at the facility, attracting researchers from all over the world. The radiological protection group at Sirius works continuously to ensure everyone's safety, in addition to shielding and monitoring, there are several security elements and one of them is the application of radiological safety training, where the researcher is presented the “Search” procedure. At the end of the training, the researcher answers a feedback form, which is used as a satisfaction survey. In the first semester for 2022, 46 people were trained of which 43.47% responded to the feedback form. Of the total responses, 95% were satisfied. Due to the large number of people attending Sirius, the radiation safety training is in the process of moving to an online format, which brings new challenges.